Description of The Meaning of Expressions in The Implementation of Famotu Ono Nihalo in Gunungsitoli - Berkat Gulo, Herni; Darnia Lase, Sensi; Tahir Harefa, Afore (CV. Multi Kreasi Media, 2024)
The purpose of this study is to decribe terms used in the Gunungsitoli, Nias, and implementation of Famotu Ono Nihalo. A deeply meaningful and culturally significant ritual for the Nias is called Famotu Ono Nihalo. The community and traditional leaders speak in a variety of ways during this rite. In order to collect data for this study, qualitative methods, including literature reviews, interviews, and observation, were used. Understanding the meaning of terms in the context of Gunungsitoli's application of Famotu Ono Nihalo is aided by this research. This knowledge can contribute to the preservation of Nias customs and culture as well as enhance Indonesia's cultural assets.